Damage resistance of aricraft wing structure using low cost carbon fibre composite materials - Zhu, Lingang (Cranfield University, 2010)
This thesis investigated the damage resistance of aircraft wing structure using low cost carbon fibre composites. Experiments had been carried out to investigate their impact behaviour, damage characteristics and residual compression strength. Current aircraft pre-impregnated materials processed by autoclave moulding and also some low-cost fibre preforms using vacuum infusion moulding were compared in this research. Novel tufting technology and veils were taken into consideration to find a cost-efficient method of improving the damage resistance of carbon fibre panels. Initial damage was induced using a falling weight (2.38Kg) apparatus mounting a 16mm hemispherical tip. Various energy levels were applied for different panels, but the energy to thickness ratio was constant. Visual inspection and ultrasonic C-scans were carried out to investigate both exterior and interior damage (fibre fracture, delamination, etc.). Micrographs of the cross-section through the impact point were employed to characterise the fracture mechanisms. The detailed Compression After Impact (CAI) procedure was recorded and presented in this thesis. In order to investigate how much ultimate compression strength was reduced by impact, plain compression strength was also measured. The behaviour of different materials, including damage size, damage shape and construction and residual compression strength were utilised in comparing the different effects on impact of different components such as fibre, fabric, interleaving of toughening layers and through thickness reinforcement. The results show that unidirectional fibre was more sensitive than woven fibre and that tufting and veils were the most affordable and efficient methods to improve the damage resistance of the laminates studied. Over 30% increase in residual compression strength was achieved via these methods.
Keywords: Carbon Fibre; Composite; Aircraft; Impact; Damage; Turfting; Interleaving; Veil; Toughened resin; CAI; Fibre fracture; C-scan; Dalamination; Mechanism